Exploring the other school: voices of school children and youth (Praxis Educativa, 2021)
The objective of this study is to analyze the processes of educational inclusion based on the voices of school children and young people (NNJE) regarding their school experience in effective and inclusive education contexts. Within the framework of a school ethnography, focus groups based on a participatory methodologywere carried out with a total of 30 students from three schools in the north of Chile. The results indicate that students want to face new school experiences, open the school to the community, improve the quality of life in the city where they live and move the classroom as the only teaching space. In addition, they highly valueinclusion as a social and educational value. The final discussions revolve around the silences and tensions visualized in the students' responses and the importance of student participation.
Keywords: student participation; educational inclusion; effective education; participatory research; school ethnography.